Role of pomegranate and citrus fruit juices in colon cancer prevention - Jaganathan, Saravana Kumar (WJG Press, 2014)
To explore the avenues in order provide a better strategic action plan that may help the Pharmacy Education to contribute for both public and private benefits. Methods: This paper adopts a qualitative research design and uses Bangladesh as a case. Qualitative methods were used that allowed interviewees to express their views in a free and personal way, giving as much prominence as possible to their thematic associations. Analysis of secondary data and intellectual debates were used with an aim of generating a discourse. Results/ Findings: The key finding shows that within the current climate; while pharmacy education provided by the public counterpart contributes producing highly skilled group who are either engaged with international market or internationally linked local companies, the private sector meets the demand of ‘diploma diseases’. Consequently, the development of community pharmacists is ignored. Within this verdict, graduates from different fields are fulfilling the market which does not allow this sector to be institutionalized for contributing largely. Conclusion: The paper argues that Pharmacy Education can be able to contribute for both public and private benefits if a realistic pattern is ensured on its operation.